Feeding niches drive different responses to plant defenses in two closely related species of classical biological control herbivores - Jasleen Kaur; Lucia Navia; Emily Kraus; Octavio Menocal; Philip G. Hahn (Biological Control)
Biological invasions threaten global ecosystems and economies, highlighting the need for sustainable management approaches like classical biological control (CBC), which involves releasing natural enemies from their native range. While releasing multiple natural enemies may enhance the CBC effectiveness, their interactions with host plant defenses remain poorly understood. This study explored the interactions between two congeneric specialist herbivores introduced to control Dioscorea bulbifera (air potato) in Florida, USA: Lilioceris cheni (Coleoptera: Chrysomelidae), primarily a leaf feeder, and L. egena, primarily a bulbil (aerial reproductive structures) feeder. We examined whether foliar herbivory by L. cheni or induced defenses by jasmonic acid (JA) or salicylic acid (SA) influenced L. egena’s feeding behavior and performance on bulbils. We conducted feeding assays to measure bulbil consumption and its relationship with pupal and adult mass as performance indicators. We used dose-dependent assays to test how varying concentrations of diosgenin, a key saponin defense compound in D. bulbifera, influenced the feeding and survival of both beetle species. Results indicated no significant differences in L. egena bulbil feeding across treatments; however, SA-treated plants produced significantly heavier pupae and adults than controls. Dose-response assays revealed non-linear, hump-shaped feeding and survival patterns in L. cheni, while L. egena’s feeding and survival decreased with increasing saponin concentrations. These findings suggest that the beetles respond differently to plant defenses while occupying distinct feeding niches, likely allowing for additive impacts on D. bulbifera. This study contributes to understanding plant defenses in CBC and informs strategies to optimize biocontrol programs for managing invasive species.